PROXIMATE AND CELLWALL COMPOSITION OF SUPER NAPIER GRASS (PENNISETUM PURPUREUM) HARVESTED AT DIFFERENT GROWTH STAGES - A. KAVYA,; G. NAGI REDDY, (The Journal of Research ANGRAU, 2025)
The investigation was conducted to find out and compare the proximate composition of Super Napier grass harvested at different growth stages which were 45 days, 60 days and 75 days during the months of January and February, 2022. The plant samples were collected at fodder unit of LFC, CVSc, Tirupati. Then, the samples were dried and ground before being analyzed for proximate composition (Moisture, Ash, Crude protein, Crude fiber, Ether extract and Nitrogen free extract) and fibre fractions (Neutral detergent fibre, Acid detergent fibre, Hemicellulose, Cellulose and Acid detergent lignin). Results of the present study indicated that, increasing the cutting interval (i.e., advancing age of maturity) increased drymatter and nutrient yields significantly (P < 0.05). In terms of nutrient content, it also increased the per cent of crude fiber (23.5, 27.1 and 30.2), acid detergent fiber (39.22, 40.08 and 41.32), neutral detergent fiber (67.12, 71.01 and 73.84), Hemicellulose (27.9, 30.93 and 32.52), Cellulose (33.52, 35.7 and 37.11) and acid detergent lignin (5.12, 5.94 and 6.62) in the plant. However, per cent of crude protein (9.78, 8.32 and 7.05) and ash (11.92, 9.56 and 7.99) was markedly decreased as the cutting interval increased. Therefore, the Super Napier at 45 days age growth is the best for harvesting which provides high nutritive value of the animal feed